Jakarta Islamic Index-L 45: Rate Financial Performance, Beta Stocks and Stock Price in Indonesian Stock Exchange - Tajus Subqi (Shirkah: Journal of Economics and Business, 2016)
This research had analyzed the effect of financial performance and stock beta (systematic risk) towards stock price of eight listed companies in Jakarta Islamic Index (JII) – LQ 45 for the time period of 2012-2014. The data was gathered by employing literature study and documentation of financial statements. Multiple regressions are used to measure the effect of independent variable towards dependent variable along with ttest and F test. The results based on overall test suggested that only ROE and NPM had opposite direction correlation with the stock price, meanwhile other variables had positive direction correlation. From partial test with 5% level of significance, only EPS and PER had significant effect on stock price while other variables had no effect. Keywords: financial performance analysis, stock price, stock beta (systematic risk), Jakarta Islamic Index